Синтаксична культура журналістського тексту (на прикладі політичного тижневика) - Шульська, Наталія М.; Shulskа, N. M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено докладний опис усіх зафіксованих помилконебезпечних синтаксичних місць, представлених у журналістських текстах політичного тижневика «Волинь-регіон». Проведено системний аналіз наявних порушень, акцентовано на найбільш частотні з них, установлено найтиповіші ненормативні місця на рівні синтаксису. У ході дослідження диференційовано мовні анормативи, що трапляються на рівні побудови словосполучення, простого і складного речення (складносурядного, складнопідрядного, безсполучникового, речення з різними видами зв’язку). The paper presents a detailed description of all fixed syntax error locations journalistic texts political newspaper «Volyn region». Carried out a systematic analysis of syntactic violations, identified the most frequent of them feature typical deviant place at the level of syntax. The study differentiated language errors occurring at the level of constructing phrases, simple and complex sentences. It was found that the rate of phrases often broken when used with prepositions designs, as well as in words, the communication connection management. At the level of a simple sentence typical errors associated with the main elements of a sentence, the sentence uniform, distinct prevalent circumstances. Among the non-regulatory entities in complex sentence structure common errors in complex sentences. In a compound sentence norm practically observed, detected single speech flaws. Of the number of errors in the compound sentence dominated errors attributive in contract, mainly unfortunate location relative to the main part of the contractor.
Syntax Culture of Journalistic Text (for Example Political Newspaper)
Keywords: синтаксис; syntax error; журналістський текст; journalistic text; політичний тижневик; political newspaper; «Волинь-регіон»; «Volyn region»